The Making of a Panorama Tune - Part III: Can Jit Hold the Lead? - Noel, Marcia (Sunday Express)
This article is Part III of Marcia Noel's experience as she has been witnessing the creative process by which arranger Jit Samaroo and Amoco Renegades are putting together the pieces of their Panorama '96 tune. In this third part, Noel reports on Renegades' winning performance at the preliminaries/ North Zone.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago